Relationship between exporters and their foreign sales and marketing intermediaries - Solberg, Carl Arthur (Elsevier JAI, 2006)
Middlemen in international markets are one of the most critical components of firms' international marketing strategy. They constitute the main link between the exporter and the local market, and are thereby the 'extended arm' of the exporter organisation. This volume of "AIM" analyses different aspects of relations between exporters and their middlemen: selection and governance, information exchange and learning, cultural aspects and finally, the dynamics of such relations. The volume should be seen as a continuation of a stream of literature that has emerged over the last five to ten years. This volume is more concerned with the phenomena under study than with casting light on one particular theoretical perspective. The contributions represented here are therefore drawing on a number of different theoretical streams: agency theory, transaction cost economics, network theory, economic sociology, resource base theory and its applied 'offspring', Internationalisation Process school of thought. It features researchers from universities in nine different countries, representing both well-established and young academicians. This is a manifest indication of the importance of this field of research. The book is an invaluable asset to students both at the graduate and doctoral levels, and should be a must for researchers in this particular field. Also practitioners will find this book stimulating in their quest for improvements to their relations with their foreign middlemen.
Keywords: Export marketing.; Distributors (Commerce) -- Foreign countries.; Export trading companies.; elektronické knihy; electronic books